Knowledge about snake venoms and toxins from Colombia: a systematic review (2023)
ABSTRACT: Colombia encompasses three mountain ranges that divide the country into five natural regions: Andes, Pacific, Caribbean, Amazon, and Orinoquia. These regions offer an impressive range of climates, altitudes, and landscapes, which lead to a high snake biodiversity. Of the almost 300 snake species reported in Colombia, nearly 50 are categorized as venomous. This high diversity of species contrasts with the small number of studies to characterize their venom compositions and natural history in the different ecoregions. This work reviews the available information about the venom composition, isolated toxins, and potential applications of snake species found in Colombia. Data compilation was conducted according to the PRISMA guidelines, and the systematic literature search was carried out in Pubmed/MEDLINE. Venom proteomes from nine Viperidae and three Elapidae species have been described using quantitative analytical strategies. In addition, venoms of three Colubridae species have been studied. Bioactivities reported for some of the venoms or isolated components—such as antibacterial, cytotoxicity on tumoral cell lines, and antiplasmodial properties—may be of interest to develop potential applications. Overall, this review indicates that, despite recent progress in the characterization of venoms from several Colombian snakes, it is necessary to perform further studies on the many species whose venoms remain essentially unexplored, especially those of the poorly known genus Micrurus.